Defiant hospitality: a grounded theory study of harm reduction psychotherapy. (2nd November 2021) - Milet, René C.; López-Castro, Teresa; Leibowitz, Amy; McGirr, Kevin; Vakharia, Sheila P.
Abstract: Harm reduction psychotherapy (HRP) is an approach to providing psychotherapy to people who use substances in which abstinence is considered neither a prerequisite to treatment nor its predominant mark of success. There is to date scant empirical research on this clinical approach despite its decades-long practice. Our study aims to spur further investigations by asking: 1) what are the basic building blocks of HRP; and (2) what theory might explain how its core strategies are unified? Eight leading HRP proponents and practitioners participated in semi-structured interviews to explore the nature of their work and how they came to it. Through an analysis of the interviews guided by grounded theory, we propose an explanatory model of HRP as practiced in the U.S. In this model, practitioners, informed by an ethos of defiant hospitality, deploy a variety of therapeutic processes whose combined, complex effects are captured in the phrase making room, which conveys opening up space while simultaneously providing safe enclosure. Making room is operationalized in processes comprising: inviting, meeting at, staying with, holding, reframing substance use, leveraging change from within, supporting agency, and signaling the limits . We discuss the model as deeply informed by its socio-historical roots within treatment spaces that participants experienced as failing to meet their clients' needs. We also consider HRP's implications for expanding the reach and capacity of addiction care for the majority of individuals with substance use disorders who may initially be unwilling or unable to abstain. Lastly, we describe its potential for furthering the field's understanding of therapeutic practice with marginalized populations.